Theophrastus of Eresus : sources for his life, writings, thought, and influence - Fortenbaugh, William W. (Philosophia Antiqua, 1992)
These two volumes represent the first fruits of an international project to produce a new collection - text, translation and commentary - of the fragments and testimonia relating to Theophrastus (c. 370-288/5 B.C.), Aristotle's pupil and successor as head of the Lyceum. The need for a new collection was apparent: the standard collection, by Wimmer, is already 120 years old, whereas we now have far better texts of many of the ancient authors in which fragments and testimonia of Theophrastus occur. Whilst classicists have devoted the past hundred years to bringing into the light the work of the major post-Aristotelian schools, the contribution of Theophrastus has remained obscure. The second printing contains corrections to the first. This first stage of the project presents the texts, critical apparatus and English translation of the fragments and testimonia. It contains a long methodological introduction, an index of Theophrastean texts and concordances with other collections (Scheider, Wimmer and the several recent partial editions). The second stage of the project, which Brill will also publish will consist of 9 commentary volumes, planned at present as follows: 1. Life, Writings, various reports (M. Sollenberger, Mt. St. Mary's College) 2. Logic (P.M. Huby, Liverpool University) 3. Physics (R.W. Sharples, University College London) 4. Metaphysics, Theology, Mathematics, Psychology (P.M. Huby, Liverpool University) 5. Human Physiology, Living Creatures, Botany (R.W. Sharples, University of London) 6. Ethics, Religion (W.W. Fortenbaugh, Rutgers University) 7. Politics (J. Mirhady) 8. Rhetoric, Poetics (W.W. Fortenbaugh, Rutgers University) 9. Music, Miscellaneous Items and Index of proper names, subject index, selective index of Greek, Latin and Arabic terms (several authors/editors). Most of the nine commentary volumes will include significant discussion of Arabic texts, with contributions by Dimitri Gutas (Yale University) and Hans Daiber (Free University of Amsterdam). It is expected that the first commentary volume, volume 5, will appear in the course of 1993.